Aid for trade, foreign direct investment and export upgrading in recipient countries - Sèna Kimm Gnangnon; Michael Roberts (World Trade Organization (WTO), 2015)
This paper examines empirically whether Aid for Trade (AfT) programmes and Foreign Direct Investment (FDI) inflows affect export upgrading and, if so, whether their effects are complementary or substitutable. Export upgrading entails export diversification (including overall export diversification, as well as diversification at the intensive and at the extensive margins) and export quality improvement. The empirical analysis shows that total AfT flows have a strong positive impact on export upgrading, and that LDCs as compared to Non-LDCs, are the most important beneficiaries of this positive impact. While the impact of FDI inflows on export diversification in host economies is mixed, these flows do exert a strong positive impact on export quality upgrading. Furthermore, the impact of FDI on export diversification is higher in LDCs than in Non-LDCs. Incidentally, AfT and FDI inflows appear substitutes (in an economic theory sense) in achieving export diversification and complementary in their effect on the improvement of export quality in recipient countries, including LDCs. Results obtained on the impact of components of total AfT are inconclusive, as they suggest both complementarity and substitutability with respect to FDI inflows in affecting export upgrading in recipient countries. Overall, empirical results suggest that AfT and FDI inflows are effective in influencing export upgrading in recipient countries. However, the results also highlight the importance of the interplay between these two kinds of capital flows in affecting export development strategies and FDI policies of recipient countries, notably LDCs. We can infer from this study that AfT flows appear to play a particularly important role in ensuring that FDI inflows do not lead to further export concentration, by putting in place the necessary conditions for export diversification.
Keywords: O24; F21; O14; 330; Aid for Trade; FDI; Export Upgrading